The role of orbiting resonances in the vibrational relaxation of I2(B,v′ = 21) by collisions with He at very low energies: a theoretical and experimental study - García Vela, Alberto (2012)
The low-energy collisions of I2(B,v′ = 21) with He involving collision-induced vibrational relaxation of I2 are investigated both experimentally and by means of wave packet simulations. The theoretical cross sections exhibit a structure of peaks originated by orbiting resonances of the I2(B,v′ = 21) − He van der Waals complex formed in the I2 + He collisions. Such a structure has similar characteristics as the structure of peaks found in the experimental cross sections. In fact, four of the five peaks of the measured cross sections appear at positions nearly coincident with those of four of the peaks found in the theoretical cross sections. Thus this result confirms the experimental finding that enhancement of I2 vibrational relaxation is caused by the population of I2(B,v′ = 21) − He orbiting resonances populated upon the low-energy collisions. The possibility of using this mechanism in the vibrational cooling of diatomic molecules is discussed.